Regional Financial Performance After the Establishment of New Autonomous Regions in Papua Province - Firdaus Failu; Mesak Iek; Hasan Basri Umar; Transna Putra Urip (Penerbit Goodwood, 2026)
Purpose: This study analyses the financial performance of Papua Province during 2020 to 2024 and assesses how the establishment of new autonomous regions in 2022 reshaped its fiscal structure. Research Methodology: A descriptive quantitative design was applied to secondary data drawn from the audited Regional Budget Realisation Reports of Papua Province. Five ratios were computed, namely fiscal decentralisation degree, regional financial independence, local own source revenue effectiveness, financial efficiency, and expenditure harmony. Each result was interpreted against established interval criteria. The ratios were analysed descriptively on a year-by-year basis, and then jointly to understand the interaction among indicators and the structural fiscal implications of regional expansion in 2022. Results: The decentralisation degree averaged 8.15 percent and independence 9.46 percent, indicating strong reliance on central transfers. Revenue effectiveness reached 106.57 percent, reflecting conservative revenue targets. Efficiency worsened to 103.41 percent after regional splitting, while operating expenditure dominated at 84.94 percent compared to 15.05 percent for capital spending. Conclusions: Papua remains fiscally dependent, and regional expansion has not significantly improved financial performance. Limitations: The five-year scope, reliance on secondary data, and exclusion of non-financial variables limit analytical depth. Contributions: The study provides a diagnostic reference for policymakers in evaluating post-expansion fiscal stress and improving regional financial governance.